Instagram: A gimmick or a serious reputation builder in the airline business? - Vinhas da Silva, R. (2021)
The purpose of the research is to shed light on the interrelatedness between Instagram and corporate reputation on the one hand and customer service expectations on the other. A conceptual model is proposed to be tested in the context of the civil aviation economy. A national flagship airline company was chosen in which to conduct the research. An online questionnaire was made available and 283 responses were collected. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test research hypotheses derived from the literature. The novelty of the work is in the scarce research found when scrutinizing the literature on possible links between Instagram and airline corporate reputation. The study found there to be a positive correlation between social media usage and corporate reputation in the airline sector. Future research needs to replicate this study across other airlines to ascertain the external validity of the current study and its potential for extrapolation.